Simulation Analysis of LED Stripes Drivers’ Influence on Electric Energy Quality - Dariusz Smugala; Pawel Ptak; Michal Bonk (Energies, 2022)
This paper presents a comparative simulation study of the operation of various types of drivers dedicated for use in light-emitting diode (LED)-based light stripes. The study comprises an experimentally verified simulation in view of their influence on harmonic content generation and impact on electric energy quality. The simulation models were optimized in order to precisely reflect the currents and voltage waveforms recorded in the frame of laboratory measurements. The simulation parameters were adjusted in view of harmonic generation analysis and high-frequency (HF) transient presence resulting from circuit principles of operation. Two driver circuit types were analyzed in the framework of the study—a voltage stabilization circuit based on a Zener diode, and a current stabilization integrated circuit (IC) based on an AL8806 chip. The study results entail an analysis executed for light stripes comprising various numbers of LEDs connected to each driver and various numbers of each of the tested drivers equipped with the same number of LEDs used as load. Based on the simulation, THD factors, harmonic components spectrum, waveform factors, power factors analysis and HF transient parameters were determined. The obtained simulations results are characterized by a high level of similarity in relation to results gained by means of measurements.